Wartości transcendentne we wspólnocie zakonnej w świetle XVI-wiecznej reguły klarysek = Transcendent values in a religious community in the light of the 16th-century monastic rule of the Poor Clares - Hawrysz, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to the characteristics of lexis associated with transcendent values that appear in the 16th-century monastic rule of the Poor Clares and its functions in the text. Thirty one words were extracted from the text. Such a small number (about 2.7% of the lexicon) is justified in the pragmatic perspective of a text whose primary purpose is to regulate the external life of the nuns which ensures uninterrupted service to God.
Keywords: polszczyzna; aksjolingwistyka; język wartości; reguła zakonna; wartości transcendentne; 16 w.; Polish language; axiolinguistics; language of values; religious rule; transcendental values; 16th century